2007
DOI: 10.1111/j.1473-2165.2007.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial grafting for vitiligo requires ultraviolet A phototherapy to increase success rate

Abstract: The success of epithelial grafting in patients with vitiligo can be increased by UVA phototherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…usually after 1 week) phototherapy was used to induce proliferation and migration of melanocytes in the recipient sites. (29)(30)(31) The repigmentation rate in these studies according to the review by Njoo et al was 87%, whereas Ozdemi et al reported rates between 25% -65%. (29)(30)(31)(32)(33)(34)(35)(36) In the study by Maleki et al, ten patients with refractory vitiligo who were treated by suction blister graft and subsequent PUVA therapy reported over 90% repigmentation in seven patients.…”
Section: Discussionmentioning
confidence: 90%
“…usually after 1 week) phototherapy was used to induce proliferation and migration of melanocytes in the recipient sites. (29)(30)(31) The repigmentation rate in these studies according to the review by Njoo et al was 87%, whereas Ozdemi et al reported rates between 25% -65%. (29)(30)(31)(32)(33)(34)(35)(36) In the study by Maleki et al, ten patients with refractory vitiligo who were treated by suction blister graft and subsequent PUVA therapy reported over 90% repigmentation in seven patients.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, this procedure is actually ''melanocyte transfer'' and the epidermis obtained through suction blisters is only a carrier [36,37]. In most studies in the literature, 1 week after the surgical procedure phototherapy was used to induce proliferation of melanocytes at the recipient sites [38][39][40]. However, in two studies the authors proved that it is not necessary for obtaining repigmentation in vitiligous areas [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the combination of epithelial grafting and psoralen plus UVA may speed up repigmentation, [11][12][13] with some starting phototherapy as early as immediately postgrafting. The most recent European Dermatology Forum consensus guidelines on vitiligo recommended that when a surgical treatment is conducted in nonsegmental vitiligo, it should be combined with UV light treatment for best outcome and long-term stability.…”
Section: In 2005mentioning
confidence: 99%